2019
DOI: 10.1155/2019/8936095
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Dopamine at Ionic Liquid Functionalized RGO/ZIF-8 Nanocomposite-Modified Electrode

Abstract: A hybrid and hierarchical nanocomposite was successfully prepared by the growth of zeolitic imidazolate framework-8 (ZIF-8) on the template of ionic liquid (IL, [Bmim][BF4]) functionalized reduced graphene oxide (IL-RGO). The structure and morphology of the IL-RGO/ZIF-8 nanocomposite were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectrometer (FTIR), and Raman spectroscopy. The results showed that RGO sheets were refrained from restacking by IL, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 53 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This indicated that the modified electrode has high selectivity as the peak current of AA and UA decreased noticeably after the addition of DA standard solution. 46,47 A recovery study was applied to verify the accuracy of the designed method by adding the DA standard solution to the urine sample. The AuNPs/PEDOT/rGO/GCE in human urine sample was investigated by standard addition technique.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the modified electrode has high selectivity as the peak current of AA and UA decreased noticeably after the addition of DA standard solution. 46,47 A recovery study was applied to verify the accuracy of the designed method by adding the DA standard solution to the urine sample. The AuNPs/PEDOT/rGO/GCE in human urine sample was investigated by standard addition technique.…”
Section: Resultsmentioning
confidence: 99%